ERGONOMIC EVALUATION OF STUDY DESKS AND CHAIRS USING ANTHROPOMETRY AND BIOMECHANICAL APPROACH AT AN-NURIYAH ISLAMIC BOARDING SCHOOL BONTOCINI JENEPONTO REGENCY - Irma Nur Afiah (Journal of Industrial Engineering Management, 2020)
School is one of the places to study. Therefore, it requires facilities to support the sustainability of the process of teaching and learning to teach such as study desks and study chairs. However, when the activity of writing is performed using study desks and chairs, students tend to lean to the front, slouch and dangle their feet. Evaluation of the products ergonomically has to be adjusted with the usage in order that they are not going to cause various negative impacts for students that will take place in both the short term and the long one. As a consequence, this study is important to carry out to minimize the mismatch of study desks and chairs with students and to obtain the redesigned results of study desks and study chairs ergonomically. The anthropometric approach was used for the dimensions of the human body in the design of study desks and chairs.  In addition, the biomechanical approach was utilized to evaluate good sitting position for students. The evaluation was observed from the calculation of compression pressure, which is the load that occurs in the neck and lumbar. The results of the design of the proposed study desks and chairs are more ergonomic and can accommodate anthropometric users; hence, parts of the study desks and chair can minimize the complaints perceived by students. Through the biomechanical approach, the results obtained the angle surface of the table of 200, the slope of the seat rest of 100º and the seat slope of 50º